2014
DOI: 10.1155/2014/549510
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Tea Tree (Melaleuca alternifolia) Essential Oil against L3 Larvae ofAnisakis simplex

Abstract: Nematicidal activity of Melaleuca alternifolia essential oil, commonly known as tea tree oil (TTO), was assayed in vitro against L3 larvae of Anisakis simplex. The results showed a mortality of 100% for concentrations between 7 and 10 μL/mL after 48 h of incubation, obtaining an LD50 value of 4.53 μL/mL after 24 hours and 4.27 μL/mL after 48 hours. Concentration-dependent inhibition of acetylcholinesterase was observed for tea tree essential oil showing inhibition values of 100% at 100 μL/mL. This fact suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
1
22
0
3
Order By: Relevance
“…This study confirms the anisakicidal activity reported for natural plants and spices used for our olive oil aromatization and also for their major compounds (β‐pinene, γ‐terpinene, 1,8‐cineole, p ‐cymene, eugenol, and limonene) . The different types of lesions observed in all dead parasites are related to the different active components, in agreement with the literature .…”
Section: Resultssupporting
confidence: 91%
“…This study confirms the anisakicidal activity reported for natural plants and spices used for our olive oil aromatization and also for their major compounds (β‐pinene, γ‐terpinene, 1,8‐cineole, p ‐cymene, eugenol, and limonene) . The different types of lesions observed in all dead parasites are related to the different active components, in agreement with the literature .…”
Section: Resultssupporting
confidence: 91%
“…Of these, tea tree oil [Melaleuca alternifolia (M. alternifolia)] gave the most significant results, killing all the larvae in 48 h at concentrations of 7 and 10 mg/mL [22]. The essential oils of several aromatic plants were found to have similarly lethal effects in 4-48 h (125 mg/ was shown to be lethal at concentrations of 250 mg/mL; and a mixture of this essential oil with chamomile essential oil displayed activity at concentrations of 187.5 mg/mL.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…This tree is native to Australia; it occurs naturally in the northern coastal region of New South Wales, bordering Queensland. TTO, which is obtained from the leaves and terminal branchlets by steam distillation, has been reported to have multiple biological activities, such as bactericidal, antiviral, antifungal, anti‐inflammatory, anti‐tumoral, analgesic, insecticidal and acaricidal activities . It is seen by many as a remedy for several skin diseases, including acne, eczema, skin infections such as herpes simplex and warts, wounds, burns, insect bites, dandruff , and nail mycoses .…”
Section: The Plant the Oil And Their Usesmentioning
confidence: 99%
“…There is an obvious terpinen‐4‐ol chemotype (type 1), an obvious terpinolene chemotype (type 2), and an obvious 1,8‐cineole chemotype (type 5). The three remaining chemotypes are dominated by the oil component 1,8‐cineole, and are considered to be 1,8‐cineole chemotypes that differ in the levels of either terpinen‐4‐ol or terpinolene present . Commercial TTOs are always of the terpinen‐4‐ol chemotype, type 1.…”
Section: Chemical Compositionmentioning
confidence: 99%